Pengaruh Media Sosial Terhadap Partisipasi Politik Masyarakat Kampus : (Studi Mahasiswa Prodi PPI FUSI UINSU) - Sari, Mayang; Zulkarnain, Zulkarnain (Jayapangus Press, 2024)
The use of social media has become an integral part of everyday life, including in people's political participation. Campus community political participation is greatly influenced by social media. Social media such as Facebook, Instagram, and WhatsApp have a significant impact on political engagement. People use social media as a political campaign tool, as well as a means of communicating and obtaining political information that is fast, accurate and reliable. This research aims to determine the influence of social media on political participation in campus communities. The method used is descriptive qualitative. The data collection method was carried out by interviewing students. Participants in this research were PPI FUSI UINSU students using structured interviews conducted with 30 PPI FUSI UINSU students. Data is collected and analyzed to identify levels of media use, participation and politics. The research results show that social media is very important for citizen participation, especially the community. The role of social media as a medium for information about politics is quite large. Social media as a communication tool for seeking political information, social media has positive and negative impacts on the political participation of campus communities, especially in increasing political awareness and participation through online information and discussions and the spread of hoax news. With easy access and fast dissemination of information, social media allows students to more easily engage in political discussions, express opinions, and gather support for various issues. Apart from that, social media also helps in mass mobilization to attend demonstrations, elections and other political events. Social media has an important role in increasing the political participation of students in the Fusion Islamic Education Study Program at UIN North Sumatra. As a result, political participation among students has become more active and dynamic, creating a younger generation who is more aware and critical of developing political issues.